A risk score for predicting death in COVID‐19 in‐hospital infection: A Brazilian single‐center study. Issue 5 (30th March 2022) - Vieira, Marcelo Luiz Campos; Afonso, Tania Regina; Oliveira, Alessandra Joslin; Stangenhaus, Carolina; Dantas, Juliana Cardoso Dória; Santos, Luiz Otávio Arruda; de França, Lucas Arraes; do Prado, Rogério Ruscitto; Cordovil, Adriana; Monaco, Cláudia Gianini; Lira Filho, Edgar Bezerra; Rodrigues, Ana Clara Tude; et al.
Abstract: Background: There is a paucity of information about Brazilian COVID‐19 in‐hospital mortality probability of death combining risk factors. Objective: We aimed to correlate COVID‐19 Brazilian in‐hospital patients' mortality to demographic aspects, biomarkers, tomographic, echocardiographic findings, and clinical events. Methods: A prospective study, single tertiary center in Brazil, consecutive patients hospitalized with COVID‐19. We analyzed the data from 111 patients from March to August 2020, performed a complete transthoracic echocardiogram, chest thoracic tomographic (CT) studies, collected biomarkers and correlated to in‐hospital mortality. Results: Mean age of the patients: 67 ± 17 years old, 65 (58.5%) men, 29 (26%) presented with systemic arterial hypertension, 18 (16%) with diabetes, 11 (9.9%) with chronic obstructive pulmonary disease. There was need for intubation and mechanical ventilation of 48 (43%) patients, death occurred in 21/111 (18.9%) patients. Multiple logistic regression models correlated variables with mortality: age (OR: 1.07; 95% CI 1.02–1.12; p : 0.012; age >74 YO AUC ROC curve: 0.725), intubation need (OR: 23.35; 95% CI 4.39–124.36; p < 0.001), D dimer (OR: 1.39; 95% CI 1.02–1.89; p : 0.036; value >1928.5 ug/L AUC ROC curve: 0.731), C‐reactive protein (OR: 1.18; 95% CI 1.05–1.32; p < 0.005; value >29.35 mg/dl AUC ROC curve: 0.836). A risk score was created to predict intrahospital probability of death, by the equation: 3.6 (age >75 YO) + 66 (intubation need) + 28 (C‐reactive protein >29) + 2.2 (D dimer >1900). Conclusions: A novel and original risk score were developed to predict the probability of death in Covid 19 in‐hospital patients concerning combined risk factors. Abstract : In‐hospital COVID 19 mortality.